Konflik Fatwa Di Malaysia: Satu Kajian Awal - Rosele, Muhammad Ikhlas; Hj Abdullah, Luqman; Hj Ismail, Paizah; Ramli, Mohd Anuar (Jurnal Fiqh, 2017)
This article focuses on existing conflicts in Islamic legal opinions (fatawa) and the scenario in some fatwa authorities in Malaysia, involving the state and national levels of institutions. Legal pronouncements from different religious institutions, including the fatawa on ESQ Leadership and Training programme, and zakat of salary, are analysed. This article identifies the factors that give rise to the conflicts including the differences in the academic backgrounds among the members of fatwa council and the different methods applied in formulating those legal opinions. This article also suggests several solutions to enhance and harmonise the formulation process of fatawa in contemporary context. The solutions encompass some proposals such as smart partnership and collaboration between fatwa institutions and higher learning institutions and appointment of Grand Mufti as the highest authority in ascertaining Islamic legal opinions. These solutions will hopefully minimise the conflicts among fatawa and avoid the confusion in the public resulting from the conflicts among fatawa in Malaysian context.